Inventory accounting at the enterprise - Koroshchenko, M. (ТДАТУ, 2021)
Stocks occupy a special place in the property of the enterprise. The efficiency of economic activity of enterprises largely depends on the evaluation and rational use of stocks.
Keywords: economy use production stocks; inventory accounting